MicroRNA-1280 modulates cell growth and invasion of thyroid carcinoma through targeting estrogen receptor Î± - Meng, D; Li, Z; Ma, X; Fu, L; Qin, G (Cellular and Molecular Biology, 2016)
Thyroid cancer (TC) is one of the most common endocrine malignancies, with a steadily increasing incidence and lethality over the last several decades. ERÎ± is a nuclear hormone receptor that has a key role in different cellular process and participates in the development and progression of thyroid cancer. ERÎ± is the predicted target gene of microRNA-1280 (miR-1280). The present study was designed to delineate the role and underlying mechanism of miR-1280 in regulating thyroid cancer through targeting ERÎ±. In our study, we analyzed the expression level of miR-1280 in thyroid cancer and detected significantly lower miR-1280 levels in TC tissue and cell lines compared with adjacent normal tissue or healthy cell line. We then overexpressed miR-1280 by miRNA mimic transfection and inhibited miR-1280 by miRNA inhibitor transfection. The inhibition of miR-1280 significantly elevated proliferation and invasion ability, whereas overexpression of miR-1280 inhibited cell growth and invasion in TC cells. Additionally, the luciferase reporter assay confirmed a targeting reaction between miR-1280 and ERÎ±. Furthermore, overexpression of miR-1280 inhibited ERÎ± and ERK pathway expression in TC cells, indicating that miR-1280 acts as a tumor suppressor by inhibiting the expression of ERÎ±. Taken together, we demonstrated that overexpressed miR-1280 levels in TC cells may promote cell proliferation and invasion by inhibiting ERÎ±, which might provide a new therapeutic target for thyroid cancer.